Heterogeneous catalyst supports - HAYES; LARRY J; BARTISH; CHARLES M (1982)
Processes are taught for the substitution of at least partially amorphous carbon with mono- and bi-dentate phosphine ligands. The ligand-substituted carbon, on combination with complexed Group VI or VIII metals, such as Wilkinson's rhodium catalyst, provide stable heterogeneous catalysts useful in reactions of the Oxo type such as hydroformylation, carbonylation and in hydrogenation.